Developing an Application for Researching the RSA Algorithm Behavior on a Multithread Platform - Nina Sinyagina (TEM Journal, 2020)
The article is focused on issues concerning the design of all needed software for researching the speed of the RSA encryption algorithm executed on a multithreaded platform. The base structure of the application is described in detail as well as the testing plan and algorithm. Shown is a method to handle and control all threads during the processes of encryption and description. The final results are visualized graphically though diagrams.